A meta-inspired termite queen algorithm for global optimization and engineering design problems. (May 2022) - Chen, Peng; Zhou, Shihua; Zhang, Qiang; Kasabov, Nikola
Abstract: This paper proposes a novel bio-inspired termite queen algorithm (TQA) to solve optimization problems by simulating the division of labor in termite populations under a queen's rule. TQA is benchmarked on a set of 23 functions to test its performance at solving global optimization problems, and applied to six real-world engineering design problems to verify its reliability and effectiveness. Comparative simulation studies with other algorithms are conducted, from whose results it is observed that TQA satisfactorily solves global optimization problems and engineering design problems.